Disability Politics and Reproductive Critique in Gayl Jones’s Corregidora - Theodora Danylevich (Journal of Integrative and Innovative Humanities, 2024)
This essay takes a reproductive justice lens, together with the analytical and liberatory insights of intersectional literary and cultural disability studies, to unearth an archive of medical eugenics exercised via non-consensual sterilization in Gayl Jones’s 1975 novel, Corregidora.My analysis also accounts for the ways in which the intimate family unit or couple can serve as a site where historical/state violence is reproduced and perpetuated, troubling the notion of a private sphere, particularly when it comes to Black Americans. Finally, I consider the stakes of such a reading of Jones’s novel for feminist health humanities and the contemporary conversation about reproductive rights and justice in the United States.